Improving Low Grade Reading Ability Using Cooperative Learning Methods - Yunitasari, Yunitasari (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
From the purpose of learning problems using the Cooperative Learning method by peeling the sequence, not only to convey information to students, it aims to convey information, among others, the formation of favorable conditions for students to improve student learning outcomes. can be developed through the Cooperative Learning method by peeling the sequence, among others, speaking, asking questions, writing, and reading. The research conducted was a Classroom Action Research (PTK) with three cycles, with each cycle consisting of two meetings. The stages of each cycle are planning, implementing actions, observing and reflecting. Each meeting is carried out a pre test and post test to determine the development of students. In the first cycle the students who completed after carrying out the post test were 59%. In the second cycle students who completed after carrying out the post test were 75 %. In the third cycle students who completed after carrying out the post test were 85%. These results indicate that thelearning model Cooperative Learning can improve the learning outcomes of low-grade students at SDN 02 Banjasari